Hubungan pengetahuan ibu tentang gizi dan praktik pemberian makanan tambahan terhadap kejadian stunting pada balita usia 12-36 bulan - Neneng Wahyuningsih; Muhammad Noris; Alkhair Alkhair; Nur Husnul Khatimah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Stunting is a nutritional problem that still occurs frequently in toddlers and can have long-term impacts on physical growth, cognitive development, and future productivity. Maternal knowledge about nutrition and appropriate supplementary feeding practices play a crucial role in meeting children's nutritional needs and preventing growth disorders. However, low maternal knowledge and inappropriate feeding practices remain contributing factors to stunting in toddlers. Purpose: To analyze the relationship between maternal knowledge about nutrition and supplementary feeding practices and the incidence of stunting in toddlers aged 12–36 months. Method: Using an observational analytical design with a cross-sectional approach, the study was conducted among mothers of toddlers aged 12–36 months in the Sori Utu Community Health Center working area. A total of 114 respondents were selected using a simple random sampling technique. Data were collected using a structured questionnaire to measure maternal knowledge about nutrition and supplementary feeding practices provision practices, while stunting status was determined through anthropometric measurements based on the height-for-age index. Data analysis was performed using the Chi-Square test with a significance level of p<0.05. Results: Most respondents had adequate nutritional knowledge (40.4%) and good supplementary feeding practices (54.4%). The prevalence of stunting in toddlers was 37.7%. Bivariate analysis showed a significant association between maternal knowledge of nutrition and the incidence of stunting (p<0.001). A significant association was also found between supplementary feeding practices and stunting (p<0.001). Toddlers whose mothers had poor nutritional knowledge and poor supplementary feeding practices were at higher risk of stunting. Conclusion: This study shows that maternal knowledge of nutrition and supplementary feeding practices are significantly associated with the incidence of stunting in toddlers aged 12–36 months. Suggestion: Further research is recommended to examine other factors associated with stunting, such as history of infectious diseases, environmental sanitation, household food security, family socioeconomic status, birth weight, and maternal nutritional status during pregnancy. Keywords: Maternal Knowledge; Nutrition; Supplementary Feeding; Stunting; Toddlers.